The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1128/jcm.35.11.2918-2922.1997
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphological transformations of Helicobacter pylori in broth media

Abstract: Helicobacter pylori, a cause of peptic ulcer disease and certain types of gastric cancers, has usually been cultured on diverse agar-based media, resulting in a requirement for 2 to 4 days of growth at 37°C. We have developed a novel broth medium consisting of a base medium supplemented with 2% newborn calf serum, Mg 2؉ , Cu 2؉ , Fe 2؉ , Zn 2؉ , Mn 2؉ , and 1 mg of lysed human erythrocytes per ml. This medium supports rapid growth of H. pylori, with a doubling time of about 50 min. Optimal growth was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 18 publications
(16 reference statements)
3
22
0
2
Order By: Relevance
“…culture used for inoculation revealed that such morphological changes are reversible. This finding is congruent with the findings that coccoid forms maintain their antigenicity [36] and that they can revert back to the spiral morphology under appropriate conditions [35]. Infecting natural hosts with cultured Helicobacter spp.…”
Section: Discussionsupporting
confidence: 89%
“…culture used for inoculation revealed that such morphological changes are reversible. This finding is congruent with the findings that coccoid forms maintain their antigenicity [36] and that they can revert back to the spiral morphology under appropriate conditions [35]. Infecting natural hosts with cultured Helicobacter spp.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that coccoid H. pylori can revert back into the helical infective form and re-grow, provided that an appropriate environment is encountered [32]. The presence of polyphosphates as an energy and phosphorous source in coccoid H. pylori may permit a certain level of metabolism to preserve vital cellular functions such as transcriptional and translational processes [33].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics of H. pylori strains cultured with the culture supernatant of S. mutans or P intermedia were examined using phase contrast microscopy as described by Andersen et al (1). Coccal cell numbers of H. pylori when cultured in the oral bacterial culture supernatant were significantly higher than those in the control.…”
Section: Atcc 43504 P11mentioning
confidence: 99%